Mechanism of action and therapeutic value of anoctamin-1 in gastrointestinal cancers - Zhang, Xiaoyue; Lin, Jie; Xu, Hongpan; Zhou, Yan; Mu, Zhiyi; Shi, Ruizhe; Lv, Yalei (Frontiers in Immunology, 2025)
Gastrointestinal (GI) cancers are main causes of poor health, with most remaining difficult to treat effectively. Identifying new targets for treatment is crucial for improving the efficacy of tumour therapies and enhancing patient quality of life. Anoctamin-1 (ANO1), a crucial component of calcium-activated chloride channels (CaCCs), is expressed widely in various cell types, including epithelial cells, vascular smooth muscle cells, and tumour cells, and influences cell proliferation and migration. Nonetheless, the exact pathways through which ANO1 contributes to malignant transformation and immune responses remain elusive. This review comprehensively examines the regulatory functions and potential therapeutic applications of ANO1 in GI cancers. The goal of this work is to offer new perspectives for further study on the role of ANO1 in gastrointestinal cancers and to support improvements in therapeutic strategies for cancer diagnosis and treatment through the targeting of ANO1.